PENGARUH MEDIA TEBAK GAMBAR TERHADAP PENGETAHUAN JAJANAN SEHAT SISWA SDN 001 TERATAK KABUPATEN KAMPAR - Eka Roshifita Rizqi; Yuni Sartika (Universitas Pahlawan, 2020)
A lot of students consumed snack that has imbalanced food quality and nutritional values. Preliminary study showed that 54,5% students at 001 Teratak elementary school had low level of knowledge on healthy snack choice. Nutrition education is needed with efficient and simple method such as guessing picture. The aim of this study was to analyze the effect of guessing picture media method on student’s knowledge on healthy snack choice in 001 Teratak Elementary School. This was quasy experimental study with a pre-test post-test control group design. 42 samples selected from 46 students in class 5 by purposive sampling technique with inclusion and exclusion criteria. Samples divided into intervention (n=21) and control group (n=21). The intervention group had guessing healthy snack choice picture while the control group had guessing ordinary pictures. Research variables were the level of knowledge in intervention and control group based on the value of the pre-test and post-test. The results showed that there was significant increase of knowledge that were given nutritional education of healthy snack choice using guessing picture media method (p